1997
DOI: 10.1016/s0735-1097(97)00223-4
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Venous Collateral Channels Causing Desaturation After Bidirectional Cavopulmonary Anastomosis: Evaluation and Management

Abstract: Angiographically detectable systemic venous collateral channels develop after bidirectional cavopulmonary anastomosis in a substantial number of patients (33% in the present series) with a variety of forms of a functional univentricular heart. Patients with venous collateral channels can be treated successfully with coil embolization, but the indications for embolization will depend on individual circumstances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 11 publications
3
78
0
4
Order By: Relevance
“…Abnormal collateral vessel development in children with C-CHD may take several forms, including systemic venous collaterals, which may be extensive, pulmonary arteriovenous malformations, or aortopulmonary collateral arteries. [16][17][18] Aortopulmonary collateral arteries associated with pulmonary atresia or severe pulmonary stenosis may lead to several problems, including significant left to right shunting and pulmonary "steal" from systemic flow during cardiopulmonary bypass. The surgical management of patients with C-CHD may be complicated by the development of the collateral vessels between the pulmonary and systemic circulation, which requires interventional cardiac catheterization or surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal collateral vessel development in children with C-CHD may take several forms, including systemic venous collaterals, which may be extensive, pulmonary arteriovenous malformations, or aortopulmonary collateral arteries. [16][17][18] Aortopulmonary collateral arteries associated with pulmonary atresia or severe pulmonary stenosis may lead to several problems, including significant left to right shunting and pulmonary "steal" from systemic flow during cardiopulmonary bypass. The surgical management of patients with C-CHD may be complicated by the development of the collateral vessels between the pulmonary and systemic circulation, which requires interventional cardiac catheterization or surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Bedard and colleagues estimated an event rate of 3.1% in a 10-year follow-up of 65 survivors after the fontan procedure (19), and Trieddman and colleagues reported that angiographically diagnosed aortopulmonary chest wall collateral vessels were present in 37% of catheterizations performed in patients who had undergone a Fontan or a bidirectional Glenn procedure (20). Veno-venous collateral channels are also a well described phenomenon after a bidirectional Glenn and most often are a reflection of elevated pulmonary arterial pressure and resistance (19,(21)(22)(23)(24). It is therefore likely that hemoptysis due to aorto-pulmonary arterial …”
Section: Brief Communicationmentioning
confidence: 99%
“…Na DCPB o fluxo sangüíneo contínuo faz-se preferencialmente para a APD e lobos inferiores (8) , podendo este fato estar associado a maior incidência de FAVP. Além disto, o desenvolvimento de circulação colateral venosa e arterial sistêmica, poderá comprometer os resultados da operação de DCPB (14,15) .…”
Section: Comentáriosunclassified
“…McELHINNEY et al (15) encontraram a presença de CCV em 33% dos pacientes submetidos a DCPB, com a maioria da drenagem realizada através da veia ázigos e hemiázigos.…”
Section: Análise Do íNdice De Mcgoonunclassified
See 1 more Smart Citation